1988
DOI: 10.1080/02786828808959170
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Trajectory Method for Determining Compositions of Particles from Major Air Pollution Sources

Abstract: Compositions of particles from several types of air pollution sources can be determined by a wind-trajectory method applied to a large data set on particle compositions obtained in St. Louis by other workers, who operated ten dichotomous samplers for 2 years and analyzed all samples by X-ray fluorescence. Samples heavily influenced by emissions from specific sources are identified by searching the data for unusually large concentrations of each element. Mean wind directions during the identified sampling perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
3
13
0
2
Order By: Relevance
“…That is, either one industry is largely responsible for the accumulation of soil Zn, Cd, and Cu values, or the accumulation is a result of aerosol deposition from a number of industries located at a specific wind direction. Because of the proximity of the Cu and Zn smelters in Sauget, it is difficult to discriminate between the two; but considering the data of Rheingrover and Gordon, 2 Sweet et al, 1 and that presented above, this evidence suggests that both emission sources may be suspect. Considering the literature data on Zn smelters, it is not at all surprising that there exists such a strong correlation between Zn and Cd.…”
Section: Correlation Resultsmentioning
confidence: 85%
“…That is, either one industry is largely responsible for the accumulation of soil Zn, Cd, and Cu values, or the accumulation is a result of aerosol deposition from a number of industries located at a specific wind direction. Because of the proximity of the Cu and Zn smelters in Sauget, it is difficult to discriminate between the two; but considering the data of Rheingrover and Gordon, 2 Sweet et al, 1 and that presented above, this evidence suggests that both emission sources may be suspect. Considering the literature data on Zn smelters, it is not at all surprising that there exists such a strong correlation between Zn and Cd.…”
Section: Correlation Resultsmentioning
confidence: 85%
“…Precipitation-and adsorption-governed dissolution where k, k 1,2 , and α are metal release rate constants determined by curve fitting. The average flow rate was calculated from the averaged flow rate data of the first four days of column operation, except where indicated, since the initial leaching characteristics were deemed most important.…”
Section: Leaching Modelsmentioning
confidence: 99%
“…Initial air quality studies showed a significant airborne concentration of hazardous and heavy metals. 1 Determining the concentration of heavy metals and metalloids (As, Cd, Cr, Cu, Hg, Ni, Pb, Sb, Sn, Zn) in the soils provided a basis for further analysis (see Part I), 2 as the soil concentration of these metals was found to be quite high in certain soils. In this study, leaching experiments were employed as a method of elucidating the association of metals to soil fractions and the mobility characteristics of contaminants under severe and natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…이러한 측정망의 경우 일반적으로 3일 또는 6일 간격으로 24시간 동안 입자상물질에 대한 시료 를 채취하고 있다 (Solomon and Sioutas, 2006). 미국 Gatz (1978), Alpert and Hopke (1981), Liu et al (1982), Chang et al (1988), Rheingrover and Gordon (1988), 그리고 Glover et al (황인조 등, 2008). 참 고 문 헌…”
Section: 국의 경우 Frm (Federal Reference Method) 측정망unclassified